MAQASHID ASY-SYARI'AH REVIEW ON FORMER CORRUPTION CONVICTS AS PROSPECTIVE LEGISLATIVE MEMBERS - Chairil, Aisyah; Sugitanata, Arif (State Islamic University of Datokarama Palu, 2022)
Abstract. This paper discusses the maqashid asy-syari'ah study of former corrupt convicts as candidates for legislative members. Specifically, it tries to dissect the reasons why corrupt convicts are allowed to become candidates for members of the legislature and examine the Maqashid Asy-Shari'ah regarding the permissibility of corrupt convicts to become candidates for legislative members. By using a literature study approach. The results of this study indicate that it is permissible for former corrupt convicts to nominate themselves as legislature members. Based on the large value of maslahah contained when it is allowed for former corrupt convicts to re-run as legislative members representing electoral districts where the community has been harmed and betrayed by the ex-convicts. This benefit is not only in the position of ex-convicts as individual Muslims or as individual citizens, but the benefits include the stability of the culture of social life in society and the maintenance of a legal system that is following ideal legal as well as in the context of realizing the principles of justice in society.